2010
DOI: 10.2174/092986710790226129
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of MicroRNAs in Heart Diseases: A Novel Important Regulator

Abstract: MicroRNAs (miRNAs) are non-coding single-stranded RNAs with about 21~23 nucleotides in length, which originate from encoding genes in nucleus. miRNAs play an inhibitory role in gene expression in a post-transcriptional level by partially complementary binding to the 3' unstranlated region (UTR) of target mRNAs. Large bodies of evidence have shown that miRNAs were involved in various diseases, such as cancer, infectious diseases, diabetes etc, and rising as critical modulators of pathological processes. Lately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 47 publications
0
33
0
2
Order By: Relevance
“…The arrhythmogenic properties of miR-1 include repression of GJA1 and KCNJ2, which encode the connexin43 and Kir2.1 subunits of the I K1 channel, respectively. 41 Moreover, overexpression of HCN2 and HCN4, which are regulated by miR-1 and miR-133, support arrhythmia-prone mechanisms. HCN2 and HCN4, which belong to the hyperpolarization-activated cyclic nucleotide-gated channel (HCN) gene family, are found in pacemaker, atrial and ventricular cells.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…The arrhythmogenic properties of miR-1 include repression of GJA1 and KCNJ2, which encode the connexin43 and Kir2.1 subunits of the I K1 channel, respectively. 41 Moreover, overexpression of HCN2 and HCN4, which are regulated by miR-1 and miR-133, support arrhythmia-prone mechanisms. HCN2 and HCN4, which belong to the hyperpolarization-activated cyclic nucleotide-gated channel (HCN) gene family, are found in pacemaker, atrial and ventricular cells.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…Although their biologic functions largely remain unclear, recent studies have demonstrated that miRNAs may function as cancer diagnosis markers and in the prediction of treatment response [7]. Not surprisingly, this aspect of cardiac biology also has been reported to be regulated by miRNAs [8,9]. In the cardiovascular system, miRNAs are not only important for heart and vascular development but also play an essential role in cardiac pathophysiology, such as arrhythmia, ischemia and coronary atherogenesis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As important regulators of heart function, miRNAs represent attractive targets/tools for treating heart disease with miR drugs [125][126][127][128][129][130][131]. The momentum in miRNA field is hyped by the large investment announced by the Coloradobased Miragen, which will initially focus on identifying targets related to CvD, primarily heart failure.…”
Section: Future Directions For Therapy Mir-diagnosis and Mir-drugsmentioning
confidence: 99%